Sulfated Alginate Reduces Pericapsular Fibrotic Overgrowth on Encapsulated cGMP-Compliant hPSC-Hepatocytes in Mice - Syanda, Adam M.; Kringstad, Vera I.; Blackford, Samuel J. I.; Kjesbu, Joachim S.; Ng, Soon Seng; Ma, Liang; Xiao, Fang; Coron, Abba E.; Rokstad, Anne Mari A.; Modi, Sunil; Rashid, S. Tamir; Strand, Berit Løkensgard (Frontiers in Bioengineering and Biotechnology, 2022)
Intra-peritoneal placement of alginate encapsulated human induced pluripotent stem cell-derived hepatocytes (PSC-Heps) represents a potential new bridging therapy for acute liver failure. One of the rate-limiting steps which needs to be overcome in order to make such a procedure more efficacious and safer is to reduce the accumulation of fibrotic tissue around the encapsulated cells to allow free passage of relevant molecules in and out for metabolism. Novel chemical compositions of alginate afford the possibility of achieving this aim. We accordingly used sulfated alginate and demonstrated this material reduced fibrotic overgrowth whilst not impeding the process of encapsulation nor cell function. Cumulatively, this suggests sulfated alginate could be a more suitable material to encapsulate PSC-hepatocyte prior to human use.